Determination of Dipicolinic Acid in "Natto" by High-Performance Liquid Chromatography Coupled With Postcolumn Photoirradiation With Zinc Acetate. (June 2019) - Mawatari, Ken-ichi; Atsumi, Motomasa; Nakamura, Fumiya; Yasuda, Makoto; Fukuuchi, Tomoko; Yamaoka, Noriko; Kaneko, Kiyoko; Nakagomi, Kazuya; Oku, Naoto
A system was developed for determining dipicolinic acid in "natto" using liquid chromatography with fluorometric detection. The compound was separated by reversed-phase chromatography using a mobile phase of 0.1 mol/L disodium hydrogen phosphate, 0.05 mol/L citric acid buffer (adjusted to pH 3.0) containing 3.0 mmol/L zinc acetate and 35 mmol/L perchloric acid. The compound in the column effluent was irradiated with ultraviolet light to produce fluorescence. This fluorescence was monitored at an excitation at 336 nm and an emission at 448 nm. The calibration curve for dipicolinic acid was observed to be linear in a range of 0.2 to 112 ng. The dipicolinic acid content of natto was 7.24 ± 0.54 mg/100 g (wet weight, mean ± standard deviation [SD], n = 6).